2020
DOI: 10.1136/bmjpo-2019-000617
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to treat pain in paediatric CFS/ME: a systematic review

Abstract: BackgroundPaediatric chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is common (prevalence 1%–2%). Two-thirds of children experience moderate or severe pain, which is associated with increased fatigue and poorer physical function. However, we do not know if treatment for CFS/ME improves pain.ObjectiveIdentify whether specialist treatment of paediatric CFS/ME improves pain.MethodsWe conducted a detailed search in MEDLINE, EMBASE, PsycINFO and the Cochrane Library. Two researchers independently scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Although pain is a prevalent symptom in individuals with CFS/ME, previous studies have not often focused on assessment of pain symptoms and specific management treatment approaches in this patient population (Ascough et al, 2020). In this vein, the present results are remarkably important, as they support the effectiveness of our online multicomponent approach to help reduce pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Although pain is a prevalent symptom in individuals with CFS/ME, previous studies have not often focused on assessment of pain symptoms and specific management treatment approaches in this patient population (Ascough et al, 2020). In this vein, the present results are remarkably important, as they support the effectiveness of our online multicomponent approach to help reduce pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Only five treatment studies included pain as an outcome measure. 10 In these studies, treatments included (CBT (cognitive behaviour therapy), a ‘self-confrontation method’, the Lightning Process and low-dose clonidine). No intervention resulted in a significant reduction in pain although two studies suggested that pain may improve in those who are ‘recovered’ compared with ‘non-recovered’.…”
Section: Introductionmentioning
confidence: 99%
“…Pain in paediatric CFS/ME is poorly understood and there are no treatments specifically targeting pain in this population. Only five treatment studies included pain as an outcome measure 10. In these studies, treatments included (CBT (cognitive behaviour therapy), a ‘self-confrontation method’, the Lightning Process and low-dose clonidine).…”
Section: Introductionmentioning
confidence: 99%